DIGITALISASI MODEL BISNIS SEBAGAI UPAYA PERUSAHAAN MENGHADAPI DUNIA DIGITAL - Ardiansyah, Dedy (Program Studi Ilmu Administrasi Bisnis, UPN Veteran Yogyakarta, 2020)
The digital world is marked by changes in the economy, companies and society to become completely digital. Economic activities that are supported by the internet, digital products and the activities of the people who constantly use the internet, have made companies have to prepare themselves to face these changes. Business digitization is carried out in stages: Organizational display, Communicational interactions, commercial transactions, integrated value and partners. While the business model consists of 4 components, namely: company strategy, customer demand, and value creation. Digitalization of the business model is carried out so that companies can face the digital world by managing how to interact with customers (Business to Consumer / B2C). Wirtz proposes the 4C model, covering: content, commerce, context and connection.